Development of cognitive behavior counseling guidelines website-based systematic desensitization techniques to overcome stress in adolescent victims of violence - Ni Putu Diah Pebriyanti; Kadek Suranata; Putu Ari Dharmayanti (Konselor, 2021)
This study aims to develop and test the validity of cognitive behavior counseling handbooks and the effectiveness of systematic desensitization counseling techniques to deal with stress in adolescent victims of violence. This research includes the development of 4D (define, design, develop, disseminate) by Thiagarajan (1974). Five people who are experts and practitioners of guidance counseling were involved in testing the validity of the guidebook. The assessment instrument used consists of 14 statement points which refer to the validity of the guidebook. Validity analysis uses the Content Validity Ratio (CVR) calculation formula from Lawshe (1975). The acquisition shows content validity (CVI) of 1 which means very good. This shows that the developed website-based systematic desensitization technique cognitive behavior counseling guidelines have met the eligibility criteria. The effectiveness test involved 30 students in this study using the one group pre-test and post-test design. This effectiveness test was carried out using the t test, the gains obtained were tcount = 17.105 and ttable = 2.048 which means that tcount > ttable, this acquisition describes that the development of cognitive behavior counseling guidelines for website-based systematic desensitization techniques is effective for dealing with stress in adolescent victims of violence.